2020
DOI: 10.1002/bjs.11442
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital triage of acute aortic syndrome using a machine learning algorithm

Abstract: Background Acute aortic syndrome (AAS) comprises a complex and potentially fatal group of conditions requiring emergency specialist management. The aim of this study was to build a prediction algorithm to assist prehospital triage of AAS. Methods Details of consecutive patients enrolled in a regional specialist aortic network were collected prospectively. Two prediction algorithms for AAS based on logistic regression and an ensemble machine learning method called SuperLearner (SL) were developed. Undertriage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Although machine learning-based prediction algorithms have shown promising results with high accuracy in other fields, including stroke and acute aortic syndrome 9 , 10 , to the best of our knowledge, only one study has reported the efficacy of a machine learning-based prediction model for the prehospital onset of ACS using only 12-lead ECG 11 . In contrast, in our study, we built the models on the basis of 3-lead ECG monitoring, as well as vital signs and symptoms, which can be easily obtained without special equipment and technical training in a prehospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although machine learning-based prediction algorithms have shown promising results with high accuracy in other fields, including stroke and acute aortic syndrome 9 , 10 , to the best of our knowledge, only one study has reported the efficacy of a machine learning-based prediction model for the prehospital onset of ACS using only 12-lead ECG 11 . In contrast, in our study, we built the models on the basis of 3-lead ECG monitoring, as well as vital signs and symptoms, which can be easily obtained without special equipment and technical training in a prehospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…A machine learning prediction model has been shown to be more accurate than prior models using LR in prehospital triage in the patients with acute aortic syndrome (AAS). 40 And this study has proved that machine learning methods are more accurate than LR in the prediction of ICU admission. Specifically, our proposed model could be used to identify patients who will be admitted to ICU postoperatively before the operation, and improve the allocation of limited ICU resources reasonably.…”
Section: Discussionmentioning
confidence: 71%
“…Of the nine studies included in the review, common prehospital data elements used in ML models targeting early detection of time-sensitive conditions or prediction of patient outcomes include the following: (1) demographics, such as age and gender; chief complaints 15 16 20 21 22 24 25 ; (2) prehospital level of consciousness such as Glasgow coma scale (GCS) 19 20 22 25 ; (3) prehospital vital signs recorded in the ambulance or in the field 16 21 22 ; (4) prehospital actions, characterized as intubation, cardiopulmonary resuscitation (CPR), and chest decompression 16 18 21 22 ; or (5) prehospital situational assessments, described as mechanism of injury, witnessed arrest or CPR initiation, and presence of speech deficit and facial and limb weakness prior to arrival to ED. 15 18 21 22 Table 1 summarizes studies using prehospital data for clinical decision-making in ED based on their targets and modeling approaches.…”
Section: Resultsmentioning
confidence: 99%
“…ML has been found to be superior in performance in terms of accuracy, specificity, and sensitivity compared with statistically calculated screening tools for sepsis prediction. 16 20 21 24 32 38 Based on current and previous definitions of sepsis, the early detection of sepsis has been linked with the following screening tools: SIRS, the modified Early Warning Scores (MEWS), and SOFA and qSOFA scores. 6 39 However, SIRS, MEWS, SOFA, and qSOFA scores when compared with ML models have performed poorly in identification of sepsis and in predicting inpatient mortality from sepsis in ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation